1976
DOI: 10.1111/j.1360-0443.1976.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure of an Experimental Treatment Program to Inculcate Controlled Drinking in Alcoholics

Abstract: SammaryThis paper reviews an out-patient pilot experiment that attempted to inculcate controlled drinking behavior in alcoholics. The methods are detailed along with some of the problems experienced and solutions invoked. The nature of a long term follow-up study is discussed and the results are presented.Thirty-five patients were referred or self-referred to the experimental program. Ten people came one time only and decided that they did not want to participate. Eleven others came less than six times, some o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In conclusion, one can only concur with Ewing and Rouse's (1976) assertion that: 'Based on our experience with these patients and a long-term follow-up, we have concluded that, in our hands at least, further attempts to inculcate controlled drinking by such methods are unjustified' (p. 134, italics added.) Their statement, it would seem, also suggests the appropriate limits of generalizability of their results.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…In conclusion, one can only concur with Ewing and Rouse's (1976) assertion that: 'Based on our experience with these patients and a long-term follow-up, we have concluded that, in our hands at least, further attempts to inculcate controlled drinking by such methods are unjustified' (p. 134, italics added.) Their statement, it would seem, also suggests the appropriate limits of generalizability of their results.…”
mentioning
confidence: 63%
“…The internal validity ofthe Ewing and Rouse (1976) study is diminished by major methodological problems, some of which become apparent only upon reading earlier descriptions of this same study (Ewing, 1972;Ewing and Rouse, 1973), Most importantly, the study was not a controlled investigation [no control subjects or control treatments were used). Further, it involved a highly selected group of subjects, Ewing (1972) initially described the study as a clinical trial conducted because he was frustrated with traditional abstinence oriented treatment methods, stating: 'The fact is that it is a rare alcoholic who will remain abstinent indefinitely and if we can offer a ray of hope, perhaps we should' (p, 12), Subjects were accepted for the study only if they had a history of failure with Alcoholics Anonymous and expressed an unwillingness to accept treatment approaches requiring total abstinence; applicants were excluded if they had a history of previous extended periods of abstinence or previous successful affiliation with Alcoholics Anonymous, Thus, the authors' 1976 description of their subject population as relatively nonselective seems at considerable variance with Ewing's 1972 statement that; 'So far I have only accepted those who have failed with Alcoholics Anonymous and with total abstinence goals, or have rejected such approaches for the time being' (Ewing, 1972, p, 9), Actually, the subjects could be described as highly recalcitrant to traditional treatment and of generally poor prognosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pendery et al (1982) has offered evidence that the conclusions reached by the Sobells failed to fit the facts of followup. It should be noted that Ewing's and Rouse's (1976) work Failure of an Experimental Treatment Program to Inculcate Controlled Drinking in Alcoholics revealed that none of their experimental subjectsalcoholicscould return to social drinking. Ewing (1979), in his guest editorial article, noted that gamma alcoholics eventually lost control (referring to his work of 1976), then added, &dquo;It is possible, of course, that a program of devoted and regular monitoring and self-scrutiny (equivalent to a long-term and deep commitment to A.A.) might have prevented the relapses.…”
Section: Proposition Iii: the Alcoholic Always Has A Choicementioning
confidence: 99%